Certificate authority system - Buenviaje, Anna Marie B. (2003)
In our present world, information is being regularly exchanged through the Internet, which is an open channel. Security during information exchange has now become a main issue. Cryptography provides security by means of encryption that makes use of encrypting/decrypting keys. The Certificate Authority System provides security and privacy in communication and information exchange. It makes use of hybrid cryptosystem, which is a combination of Secret Key Cryptography and Public Key Infrastructure. The system uses both session key and key pairs for encryption and decryption to provide effective security. It creates and verifies digital signatures to provide authentication and non-repudiation.